An ontology for software component matching - Pahl, Claus (International journal on software tools for technology transfer, 2007)
Matching is a central activity in the discovery and assembly of reusable software components. We investigate how ontology technologies can be utilised to support software component development. We use description logics, which underlie Semantic Web ontology languages, such as OWL, to develop an ontology for matching requested and provided components. A link between modal logic and description logics will prove invaluable for the provision of reasoning support for component behaviour. [PUBLICATION ABSTRACT]